Strategi Komunikasi OIC Youth Indonesia dalam Meningkatkan Kualitas Pemuda Muslim melalui Program Kepemimpinan - Rahma Putri Rahayu; Pia Khoirotun Nisa (Fakultas Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatullah Jakarta, 2021)
The Indonesian Islamic Cooperation Youth Organization is a youth organization that builds the quality of youth through leadership programs. As in IIYLS 2019, there are two agenda of activities, namely the OIC Model and YES. Methods in this research are qualitative. Data collection techniques consist of observation, interviews, and study documentation to be analyzed in the descriptive data analysis technique. Laurie J. Wilson and Joseph D. Odgen about the stages of communication strategy. There are four stages on Research, Action Plans, Communication and Evaluation. The results of this study indicate that the strategy research conducted by the Youth Organization of Indonesian Islamic Cooperation has been going well. This is evidenced by the formation of a leadership program team, coordination and cooperation with the government that is managed, the use of appropriate publication media, as well as the packaging of interesting activity programs.